2014
DOI: 10.2320/matertrans.m2014013
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Properties of Polyethyleneimine Film Coated on a SiO<sub>2</sub> Substrate in Different Concentrations

Abstract: Angle-resolved X-ray photoelectron spectroscopy (AR-XPS) and atomic force microscopy (AFM) were employed to investigate the detailed surface bonding structure and morphology of polyethyleneimine (PEI) layers coated on a SiO 2 substrate in concentrations of 0.5 10.0 mass%. With an increase in the PEI concentration, the CN bonds corresponding to the imine group (NH) became dominant in the PEI layers, implying a characteristic feature to verify the immobilization of PEI on the SiO 2 surface. The thickness of PEI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The appearance of CN corresponds to CN bonds in PEI, clay modified with APTMS and covalent linkage between epoxy and amine. These assignments are in well agreement with the literature …”
Section: Resultssupporting
confidence: 93%
“…The appearance of CN corresponds to CN bonds in PEI, clay modified with APTMS and covalent linkage between epoxy and amine. These assignments are in well agreement with the literature …”
Section: Resultssupporting
confidence: 93%
“…The QCM crystals were coated beforehand with a polyethyleneimine monolayer. The effect of this layer on the QCM experiment can be neglected due to its low thickness of 0.6 nm 37 . NPan and CNF were adsorbed during the QCM experiment onto the polyethyleneimine-coated QCM crystals through electrostatic interactions ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The amount was 0.64 ± 0.252 μg/cm 2 , indicating that a PEI layer of 6.4 nm thickness adhered to the Au surface, assuming its density to be 1.03 g/cm 3 16 . This thickness is much greater than that of a PEI monolayer coating (~0.6 nm) 14 , which suggests aggregation of the PEI layer. Scanning electron microscopy (SEM) confirmed that the O 2 plasma-treated Au electrode was covered with a non-uniform coating of PEI.…”
Section: Resultsmentioning
confidence: 78%
“…The slight negative shift of the Au 4 f peaks indicated that the gold surface was reduced by the non-protonated amino groups of PEI 13 . The positive shift of the C = O peak after PEI adsorption indicates the interactions between C = O and the positively charged amino groups of PEI 14,15 . These results show that the PEI layer interacts with both the carbonyl groups present on the treated surface and the Au metal surface.
Figure 2XPS spectra of ( a ) N 1 s, ( b ) C 1 s of a PEI-O 2 Au electrode, and ( c ) C 1 s of an O 2 Au electrode.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation